Evaluating Hydraulic Properties of Biochar‐Amended Soil Aggregates by High‐Performance Pore‐Scale Simulations. Issue 1 (12th January 2018) - Zhou, Hongxiang; Yu, Xiuling; Chen, Cheng; Zeng, Lingzao; Lu, Shenggao; Wu, Laosheng
Abstract : Core Ideas: SR‐mCT was used to characterize soil pore structures. Graphics processing unit–enhanced LBM was used to simulate the water flow. Effects of biochar amendment on soil hydraulic properties were evaluated. Biochar amendment can change the soil pore architecture and improve soil physical and hydraulic properties. In this study, two clayey soils were selected and treated with or without biochar amendment (four treatments). Synchrotron‐based X‐ray micro‐computed tomography (SR‐mCT) was used to characterize pore structures of the selected aggregates from the treatments. Based on the high‐resolution soil pore structure information, the three‐dimensional lattice Boltzmann (LB) method was used to simulate water flow in pores. The high‐resolution soil pore structures were also used to define the internal boundary conditions in the LB method that was accelerated by graphics processing unit parallel computing. Results showed that biochar amendment increased soil permeability by at least one order of magnitude, reduced tortuosity by 20 to 30%, and resulted in more uniformly distributed pore water velocities, which was attributed to the change in soil pore geometry. This study is the first physically based modeling effort to assess the effect of biochar amendment on hydraulic properties of soil aggregates. The SR‐mCT method and modeling approach developed in the research play an important role in understanding the mechanisms of water and nutrient transport in soil at the pore scale.